Principles and Products of Islamic Finance - Hans Dieter Seibel; Omar Imady (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2006)
The principles of Islamic finance are laid down in the sharia, Islamic law. Islamic finance, comprising financial transactions in banks and non-bank financial institutions formal and non-formal financial institutions, is based on the concept of a social order of brotherhood and solidarity. The participants in banking transactions are considered business partners who jointly bear the risks and profits. Islamic financial instruments and products are equity-oriented and based on various forms of profit and loss sharing. As Islamic banks and their clients are partners, both sides of financial intermediation are based on sharing risks and gains: the transfer of funds from clients to the bank (depositing) is based on revenue-sharing and usually calculated ex post on a monthly basis1; the transfer of funds from the bank to the clients is based on profit-sharing (lending, financing), either at a mutually agreed-upon ratio as in the case of mudarabah or at a mutually agreed-upon fixed rate. Such ratios and rates vary between institutions and may also vary between contracts within the same institution, contingent upon perceived business prospects and risks. Islamic banking finances only real transactions with underlying assets; speculative investments such as margin trading and derivatives transactions are excluded. Lending, or financing, is backed by collateral; collateral-free lending would normally be considered as containing a speculative element, or moral hazard. Similarly, to avoid speculation and moral hazard, normally only investors with several years of successfully business experience are financed. The paying or taking of riba, interest, is prohibited.
Keywords: 330